Impact of the “WeChat Cloud Service” Option for Patients in an Emergent Intensive Care Unit During an Epidemic in Tai Zhou China - Wang, Jie; Qin, Jie; Tung, Tao-Hsin; Chen, Jianping; Zheng, Ningyu; Lu, Lili; Jin, Yingying (Frontiers in Medicine, 2022)
To explore the application and effect of “WeChat cloud service” in the emergency intensive care unit (EICU) in the context of an epidemic, we examined 774 patients admitted to an EICU between February 2020 and June 2021. Patients admitted from February 2020 to December 2020 were selected as the control group (n = 503) and those from January 2021 to June 2021 comprised the observation group (n = 271). There were no statistically significant differences in gender, age, disease, and length of stay in the EICU between the groups. The control group received the general (routine) daily service, such as communicating with families through in-person information transmission, and receiving self-provided drugs and daily supplies during the specified visiting time; the observation group received the “WeChat cloud service” providing the chance of communication, supplies, and payment through the platform at any time. We used a T-test and χ2-test to analyse the incidence of delirium, labour costs, and patient and family satisfaction throughout ICU treatment for comparison. Results indicated that the observation group had lower labour costs, less incidence of delirium, and greater patient and family satisfaction than the control group. The “WeChat cloud service” was beneficial for preventing and controlling coronavirus disease 2019 during the epidemic and providing an improved patient experience.